E-LKPD BERBASIS INQUIRY PADA MATERI ARITMATIKA SOSIAL - Amnah; Aima, Zulfitri; Delyana, Hafizah (Universitas Muhammadiyah Metro, 2024)
This research is based on the lack of technology and communication in the mathematics learning process and the teaching materials used at SMP Negeri 8 Natal, namely package books, but the package books still cannot guide students in the learning process. The purpose of this study is to produce inquiry-based E-LKPD on social arithmetic material. This type of research is development research using R&D (Research & Development). The development model used is the Plomp development model. The instruments used in the preliminary research stage are student characteristics questionnaires, interview guidelines and observation questionnaires while the instruments in the prototyping phase stage are self-evaluation questionnaires, validity questionnaires and interview guidelines for the use of inquiry-based E-LKPD. Based on the validator's assessment, the validity of the E-LKPD by Mathematicians and Technologists was obtained at 90.3% with the category of very valid. Based on the results of the study, it can be concluded that inquiry-based E-LKPD on social arithmetic material is declared valid for use by teachers and students.